Defining Petrophysical Properties of Ultramafic and Mafic Rocks In Terms of Alteration. Issue 1 (1st December 2018) - Adams, Cameron; Dentith, Michael
Abstract : The effects of talc-carbonate alteration and serpentinisation on the physical properties of ultramafic rocks are regularly presented but often as incomplete datasets, and are subsequently poorly understood. The development of integrated and more robust physical property databases is important. Consequently, two Western Australian greenstone terranes have been studied. Data from ~2, 000 samples taken from the Plutonic-Marymia Greenstone Belt and the Eastern Gold Fields are presented. New p-wave velocity, magnetic susceptibility, density, apparent porosity, and natural remanent magnetisation data are examined. An integrated approach of placing empirical petrophysical data within a rigorous mineralogical and petrological framework has been undertaken. The use of Short Wave Infrared (SWIR) spectral data is investigated. SWIR data are shown to be useful for the identification and quantification of talc-carbonate mineralogy of ultramafic rocks. Similarly the identification of variable Mg-Fe chlorite is also beneficial. Petrophysical data are shown to correlate well when compared with talc-carbonate and chlorite spectral mineral data and abundances. Serpentine group mineralogy can be identified, however olivine, quartz and pyroxene minerals are unable to be resolved due poor absorption features in the SWIR. Serpentine mineral species, i.e. lizardite, antigorite, and chrysotile, are also unable to be resolved due to narrowness of wavelength absorption features. It also important to recognise that reported mineral abundances are typically normalised to SWIR active minerals. Anomalous values of reliable but limited spectrally classified serpentine data have shown two populations of serpentinised rocks within acoustic impedance plots. In particular, one population presents a high p-wave velocity, i.e. 6500-7000m/s, and ubiquitously low density and high magnetic susceptibility. These data suggest the presence of antigorite and or silicification. Consequently, although SWIR classified data have been shown to be appropriate to use for interpreting variable degrees of talc-carbonate alteration, an interpretation of serpentinised rocks should be treated with caution. Furthermore, it is recognised that the uncertainty of SWIR mineral abundance data should be evaluated where SWIR active minerals present overlapping wavelength features.